Fútbol Extremo - Jake Maddox (Stone Arch Books, 2020)
Andre Makuza is excited for another championship season with his middle school summer soccer team. But a new coach is taking over, his unusual training methods have the team feeling frustrated. Will the coach's oddball ways ever lead to victory, or is the soccer switch too much for Andrea and his teammates to handle?
Keywords: Sports Stories -- Sports Stories